Potentially unsafe doses of local anesthetics in axillary brachial plexus block: A single-center retrospective cohort study - Mélanie Suppan; Caroline Flora Samer; Georges Louis Savoldelli (PLoS ONE, 2026)
Local anesthetic systemic toxicity is a rare but potentially life-threatening complication of regional anesthesia that can occur when high doses of local anesthetics are administered. This study aimed to evaluate the frequency of local anesthetic doses exceeding safe thresholds in axillary brachial plexus blocks using four different calculation methods. This retrospective study analyzed 2395 patients who underwent axillary brachial plexus block between 2017 and 2021 at Geneva University Hospitals. Four progressively more conservative sets of dosing rules were systematically applied. These included standard package insert recommendations, weight-based limits using actual weight, weight-based limits using ideal body weight, and consensus-based rules adapted to patients’ comorbidities and treatments. For local anesthetic mixtures, proportional calculations were applied to determine cumulative maximum safe doses. Using the most conservative calculation method, local anesthetic doses exceeded maximum safe thresholds in 64.8% of cases, compared to 29.5% using package insert recommendations. Potentially unsafe doses were consistently more frequent with local anesthetic mixtures (85.4%) compared to single agents (32.4%) across all calculation methods. Symptoms compatible with local anesthetic systemic toxicity occurred in 19 patients (0.79%), with severe manifestations in 9 cases (0.38%). No significant relationship was found between these symptoms and potentially unsafe doses, regardless of the calculation method used. This study reveals substantial variation in local anesthetic dosing practices for axillary brachial plexus blocks. Rates of potentially unsafe doses varied significantly depending on the criteria applied. The consistent pattern of higher rates of potentially unsafe doses with mixture use highlights opportunities for practice standardization and improved safety protocols in regional anesthesia. The multiple calculation approaches allow clinicians to compare findings with their own institutional practices.